Data Visualization of Kemplang Sales Using Looker Studio at Arion Souvenir Shop - Yuda Restu Fauzi; Budi Sutomo (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Arion Souvenir Shop, located in Metro City, offers grilled kemplang snacks, a traditional Indonesian delicacy. The shop encounters several challenges, including the difficulty in revealing actual monthly sales trends, identifying the most popular kemplang variants, and detecting the annual sales cycle. Grilled kemplang is available in three variants: jumbo, medium, and small. To address these challenges, this study visualizes kemplang sales data for the years 2022–2024 using Google Looker Studio. The visualization includes various graphical formats such as bar charts, pie charts, pivot tables, and line charts. The results of the analysis show that sales were consistently highest in January across the three years, indicating a strong seasonal trend. Additionally, the small kemplang variant emerged as the most popular choice, consistently outperforming the other variants in monthly sales. The study also observed a slight decline in overall sales over the three-year period. This research contributes significantly to the analysis of local product sales data by leveraging Looker Studio for interactive trend visualization. It provides practical recommendations for local business owners and empirical evidence on the application of data visualization tools in strategic decision-making. The insights gained from this study can help businesses optimize their sales strategies, improve inventory management, and enhance customer engagement